Lesson Study as Professional Development of Early Childhood Educators - Farida Samad; Mohamad Syarif Sumantri; Nurbiana Dhieni (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to examine lesson study activities to improve early childhood educators’ professionalism. This is qualitative research study. The lesson study, conceived as a professional development approach focused on collaboration and reflection, took place in the 5th semester of the 2020/2021 academic year and involved 25 participants. The instrument of the study consisted of lesson design, field notes, and interviews with the observers, as well as the transcription of the audio recording. To analyze the data, the technique is a qualitative data analysis developed by Miles and Huberman consisting of three stages performed sequentially those are: 1) data reduction, 2) presents data, 3) draw conclusion. The research results can be used as a basis in improving and strengthening a lesson study activities dealing with make up- and beauty activities. It made a significant positive contribution to the professional development of educators in various aspects such as lesson design, methods and course evaluation.